1972
DOI: 10.1111/j.1432-1033.1972.tb01691.x
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Structure of L‐Lactate Dehydrogenase (Cytochrome b2) of Saccharomyces cerevisiae

Abstract: The molecular weights of yeast L‐lactate dehydrogenase (cytochrome b2) and of its polypeptide chains have been measured by ultracentrifugation. The intact protein was found to have a molecular weight of 240000 ± 10000 by sedimentation equilibrium measurements according to the Yphantis high‐speed method. The solution obtained by dissolving the protein in 6 M guanidine (with added 2‐mercaptoethanol) behaved as if it were monodisperse, giving Mr= 31300 ± 2000, by approach‐to‐equilibrium measurements. This result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 22 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…8) [9,43,44]. Preliminary reconstitution experiments with the partly purified m and ,!j subunits of cleaved cytochrome b, also suggested that haem binding occurred preferentially on the m subunit, whereas the evidence concerning the FMN binding site looked rather weak [27]. However, even before conclusive experimental evidence becomes available, it now seems quite probable that it is located on the segment corresponding to the light chain of the cleaved enzyme for the reasons that follow.…”
Section: Discussionmentioning
confidence: 99%
“…8) [9,43,44]. Preliminary reconstitution experiments with the partly purified m and ,!j subunits of cleaved cytochrome b, also suggested that haem binding occurred preferentially on the m subunit, whereas the evidence concerning the FMN binding site looked rather weak [27]. However, even before conclusive experimental evidence becomes available, it now seems quite probable that it is located on the segment corresponding to the light chain of the cleaved enzyme for the reasons that follow.…”
Section: Discussionmentioning
confidence: 99%
“…Flavocytochrome b2 [L-lactate:ferricytochrome c oxidoreductase, EC 1.1.2.3] from baker's yeast (Saccharomyces cerevisiae) is a tetrameric enzyme of Mr 230,000 (1) and is located in the intermembrane space of mitochondria (2). Each subunit of Mr 57,500 (3) contains one heme and one FMN, both bound noncovalently (4).…”
mentioning
confidence: 99%
“…Yeast L-lactate :cytochrome c oxidoreductase, commonly referred to as flavocytochrome b,, consists of a tetramer [3,4]. Each protomer contains one flavin mononucleotide and one protoheme [5] coordinated by two histidine residues [6].…”
mentioning
confidence: 99%